Comparison of MALDI-TOF MS, nucleic acid hybridization and the MPT64 immunochromatographic test for the identification of M-tuberculosis and non-tuberculosis Mycobacterium species - (:unkn) unknown (EDIZIONI INT SRL, 2016)
Mycobacteria are an important cause of morbidity in humans. Rapid and accurate mycobacterial identification is important for improving patient outcomes. However, identification of Mycobacterium species is not easy, due to the slow and fastidious growth of mycobacteria. Recently, biochemical, sequencing, and probing methods have come to be used for identification. This study compared the performance of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) for the identification of M. tuberculosis and non-tuberculosis Mycobacteria (NTM) to those of nucleic acid hybridization (NAH) and the MPT64 immunochromatographic test. A total of 69 isolates from Marmara University Hospital, Microbiology Laboratory obtained between 2012 and 2013 were included in our study. All strains were grown on Lowenstein-Jensen and Middlebrook 7H9 medium. Among the 69 isolates, 56 (81%) were isolated as Mycobacterium tuberculosis complex (MTC), and 13 (19%) were isolated as NTM by the MPT64 ICT. NAH was able to identify all isolates to the species level. The isolated NTM included M. intracellulare (n: 5), M. lentiflavum (n: 3), M. xenopi (n: 2), M. malmoense (n: 1), M. abscessus (n: 1), and M. avium (n: 1). MALDI-TOF MS identified 88% of the mycobacterial isolates. All M. tuberculosis strains were identified correctly, but the ratio was 38.5% for NTM. Mycobacterial identification using MALDI-TOF MS takes 45 minutes and costs 3 Euro/test, whereas mycobacterial identification using NAH takes 6-7 hours and costs 30 Euro/test. In conclusion, MALDI-TOF MS has the potential to identify mycobacteria in the clinical laboratory setting by reducing identification turnaround time and laboratory costs for isolate referral.
Keywords: Mycobacteria; MALDI-TOF MS; MPT ICT; Nucleic acid hybridization; DESORPTION IONIZATION-TIME; MASS-SPECTROMETRY; RAPID IDENTIFICATION; CULTURE-MEDIA; DIRECT ASSAY; COMPLEX